(3JOQjS GdadSaI aj GdhWf GdYQHj Hjf eWGdH GdJZjjQ heUGYH GdhGbYs - (3MehO, LeGds ((3HjQhJs (3eQcR OQGSGJ GdhMOI GdYQHjIs, 2015)
(3jgOa GdebGd Edi WQM eG jLH GdbjGe Hg Ydi GdeTJZdjf HGdadSaI aj GdhWf GdYQHj , ERGA GdhGbY GdLOjO GdeJYdb HGdeWGdH GdJj QaYgG GdTHGH GdPjf MedhG dhGA GdJZjjQ aj GdHdOGf GdYQHjI(B. (3JYGdL GdebGdI ChdG MbjbI GdJZjjQ aj GdeLJeYGJ GdYQHjI eHjfI Cf GdJZjjQ GdPj UGQ eWdhHG HYO eG oSqej HGdQHjY GdYQHj jfHg HVQhQI JLGhR GdCSGdjH GdJbdjOjI aj eYGdLI eTcdI GdJfejI, hGdJfHg Edi Cf GdJfejI GdMbjbjI dG Jcef aj SO MGLGJ GdEfSGf GdeGOjI abW, Hd hef HGH Chdi aj ETHGY MGLGJg GdKbGajI hGdQhMjI HMjK JUjQ gPg GdMGLGJ aj Sqde ChdhjGJ Cj eTQhY Mbjbj ddJZjjQ(B. (3Ke JYQV GdebGdI hGbY GdadSaI aj GdeLJeYGJ GdYQHjI HOAG HGdeSJhi GdeLJeYj GdYGe MjK jQi GdeDda Cf GdadSaI eG JRGd HYjOI ef Cf JDqOj Cj OhQ JZjjQj aj eNJda efGMj GdMjGI GdGLJeGYjI hGdSjGSjI hGdKbGajI dhLhO YbHGJ efgG eG jJYdb HWHjYI GdadSaI, Ch eG jJYdb HGdfXQI Edi GdadSaI ef GdefXhQ GdJbfhHjQhbQGWj Ch GdefXhQ GdJbdjOhj GdeSJMOK(B. (3Ke JfJbd GdebGdI Edi YQV hGbY GdadSaI Ydi eSJhi GdOQS GdadSaj hYdi eSJhi GdfbO GdehLg Edi GdOQS GdadSaj HUaI YGeI, h eSJhi GdfbO GdOGNdj ajeG jJYdb HeG JJHfGg HYV GdBQGA hGdGJLGgGJ GdJYdjejI aj GdadSaI, h eSJhi NWGH GdeOQS heSJhi GdhVY GdeJCqRe aj efXheJfG GdJQHhjI(B. (3hJNJe GdebGdI HGdJQcjR Ydi C f GdGgJeGe HGdadSaI cWQjbI efgLjI aj GdJacjQ GdMqQ hGdfbOj gj hMOgG GdJj JYWj ddJZjjQ eOdhdg GdhGSY, MjK Jchf adSaI GSJKeGQ aj GdQCSeGd GdHTQj HGYJHGQg KQhkI eGOjI heYfhjI YGdjI GdbjeI hGdeQOhOjI, EP JCNP aj GdGYJHGQ Cf dgPG GdEfSGf hLgkG BNQ ZjQ Pdc GdhLg GdPj jbqjOg HdZI GdCQbGe hGdhbGFY GdeGOjI(B.s
(3GdfhY (B: (3ebGds
Keywords: Arab Countries; Educational prospective; L$1 (Benseignement de la Philosophie et la Morales; Pays Arabes; Philosophy and Moral Education; Prospective; (3GdGSJTQGas; (3GdOhd GdYQHjIs; (3JYdje GdadSaI hGdGNdGbs